Pengaruh Kualitas Layanan Toko Terhubung Terhadap Kepuasan dan Loyalitas Pelanggan - Hardiansyah, Muhammad Febri; Nugroho, Sahid Susilo (Benefit: Jurnal Manajemen dan Bisnis, 2012)
The study aims to examine the relationship between buying environment characteristics, esatisfactionand e-loyalty referring to the research model from Kim et al. (2009) that is applied to apparel product category in the US as a developed country. The study offers a new empirical perspective by investigating electronic product category in Indonesia as adeveloping country.The study conduct a survey method to reach a purposive sample of 200 consumers from 4big cities in Indonesia that are Jakar ta, Bandung, Yogyakarta and Surabaya. The findingsprove that among six online service attributes, only convenience and information caninflluence e-satisfaction significantly. Web appearance, entertainment value, communication and customization are failed to be a significant predictors of e satisfaction. In the next step, e-satisfaction influences e-loyalty significantly.